Features of the Evolution of {4}He{+} Ion Flux in Yttrium Iron Garnet in the Channeling Mode - Malyutin V. M. Vasiliy Mikhailovich (Plasma, Microwave, Ion, Electron and Isotope Technologies, 2015)
Title screen